Kompetensi Auditor dan Efektivitas Audit Syariah Internal dengan Dukungan Senior Manajemen sebagai Moderasi - Yetri Martika Sari; Shinta Widyastuti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2022)
The phenomenon of the lack of competence of internal Shariah auditors became the basis for the development of this research with the aim to test the influence of competence on the effectiveness of internal Sharia audits taking into account the role of senior management support. The research data was collected using questionnaires and obtained by 34 respondents who were internal auditors at four Islamic commercial banks in Indonesia. The study used a quantitative approach and statistical testing was conducted using smartpls. The results of this study confirm that competence has no effect on the effectiveness of internal Sharia audits and senior management support does not moderate the relationship between competence and effectiveness of internal Sharia audits. Senior management support is identified as homologizer moderation. This research provides insight that the effectiveness of internal Sharia audits will not be realized if the competence of internal auditors is not improved, especially competence related to auditor knowledge about sharia / fiqh muamalah or sharia audit that can be proven by ownership of certification related to sharia. If you want the effectiveness of internal Sharia audit to increase then senior management can design continuing education for its employees to improve competence in the field of Sharia / fiqh muamalah / sharia audit